Answers

2015-06-24T21:45:21+05:30
Take (x-y) as a
4a^2-12a+9
4a^2-6a-6a+9
2a (2a-3)-3 (2a-3)
(2a-3)(2a-3)
(2x-2y-3)(2x-2y-3)
0
It could have been simplified further dude
2015-06-24T21:50:51+05:30
Let x-y be s.
Therefore, the expression becomes
4s^{2} -12s+9
=(2s)^{2} - 2*2s*3+(3)^{2}
=(2s-3)^{2}
Substituting s as x-y (as mentioned above) we get:
[2(x-y)+3]^{2}
=(2x-2y+3)^{2}
Ans:=(2x-2y+3)^{2}
-----------------------------------------------------------

1 5 1
Please mark as the best click on the yellow button below my answer